Layer by layer assembly of flame retardant thin films on closed cell PET foams: Efficiency of ammonium polyphosphate versus DNA. (March 2015) - Carosio, Federico; Cuttica, Fabio; Di Blasio, Alessandro; Alongi, Jenny; Malucelli, Giulio
Abstract: The present work aims to investigate the layer by layer deposition of flame retardant thin coatings on closed cell polyethylene terephthalate foams. To this aim, two coating architectures have been selected in order to evaluate the efficiency of ammonium polyphosphate (APP) versus the freshly proved flame retardant deoxyribonucleic acid (DNA). Both the selected architectures were able to homogeneously coat the external surface of the foams; APP-based coatings yielded average thicknesses around 450 nm while DNA based counterparts reached 340 nm. Flammability and cone calorimetry tests clearly demonstrated the superior performances of APP-based coatings. Indeed, only these latter were capable of suppressing the melt dripping behavior typical of PET and reducing the heat release rate peak by 25%.